Tarfala daily mean temperature series 1965- - Peter Jansson (Stockholm University, 2016)
This data set consists of daily mean temperatures recorded at Tarfala Research Station since 1965. The record is an assembly of automatically recoded air temperatures. Measurement devices have changed over time as the equipment has been modernized. Please refer to the annual meteorological measurements reported from Tarfala Reseearch Station for more detailed information. The data is provided as is. The data includes breaks indicated by a "Not-a-Number", "NaN" value. Since 1995, the Swedish Meteorological and Hydrological Institute, SMHI, maintains an official station (Tarfala A; Climate number: 178970; WMO-number: 2-29) in close proximity to the Tarfala meteorological site. It is therefore possible to use data from the SMHI station to fill in gaps in the TRS record.
Keywords: Atmospheric Sciences; 40199 Atmospheric Sciences not elsewhere classified; 40105 Climatology (excl. Climate Change Processes); Climate Science; 49999 Earth Sciences not elsewhere classified; Other Earth Sciences; Annan geovetenskap; Climate Science; Klimatvetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap